IBD care in Europe: A comparative audit of the inpatient management of Crohn's disease and ulcerative colitis using the national UK IBD audit tool. - Cassinotti, A; Keshav, S; Ardizzone, S; Mortensen, N; Sampietro, G; Fociani, P; Duca, P; George, B; Lazzaroni, M; Manes, G; Warren, B; Foschi, D; et al. (2009)
BACKGROUND AND AIMS: The National UK IBD audit tool is an electronic database created to improve the quality and safety of care for IBD patients by auditing individual patient care, service resources and organisation against national standards. We used the National UK IBD audit tool to compare the organisation and process of IBD care between services in Oxford (UK) and Milan (Italy), as a pilot study to evaluate its application outside national boundaries. METHODS: Clinical and demographic data of patients with CD and UC, consecutively admitted during a 2month period, were collected and compared between the centres, to each other and to the UK IBD standards obtained by previous audit analyses performed in Oxford in 2006. RESULTS: 20 and 26 patients with UC were admitted in Oxford and Milan, as well as 21 and 20 patients with CD, respectively. Most admissions in Milan were planned admissions for moderately active treatment-refractory disease. No patient died. Oxford had a higher surgery rate. Endoscopy for UC consisted mainly of colonoscopy in Milan (92%) and flexible sigmoidoscopy in Oxford (64%). In CD, Oxford data revealed a higher use of immununomodulators and CT scan, compared with higher use of bowel ultrasound in Milan. CRP was the preferred biomarker of disease activity. The following areas did not reach the standards set for the 2006 UK IBD Audit: the lack in Milan of IBD specialist nurses and few dietitian visits, as well as little attention to heparin prophylaxis and abdominal radiography in UC. Both sites paid little attention to stool cultures and revealed a high rate of active smokers in CD and little attention to bone protection in steroids users. Since the 2006 audit in Oxford, improvements include IBD specialist nurse visits, dietitian visits, number of active smokers, stool samples, prophylactic heparin, bone protection and nutritional assessment. CONCLUSIONS: Consistent procedural differences between Oxford and Milan identified by audits of both UC and CD could be resolved by organisational change, with an improvement in the service. The UK IBD audit tool is an easy instrument to assess the processes and outcomes of care delivery in IBD and can be applied also outside UK.